Transannular cascade approaches to diterpene analogues - Lahdenpera, A (2017)
Abstract The aim of this project is to apply the chemistry developed in our group and to extend it to asymmetric transannular methodology for the generation of different fused, diterpene like, polycyclic ring systems. Construction of these ring systems is predicated on an intramolecular Michael reaction cascade or an ionic Diels Alder reaction catalysed by chiral quaternary ammonium salts under basic phase transfer conditions. We demonstrate a rapid synthesis of the transannular cascade precursor that undergoes cyclisation producing three new stereocenters in high enantioselectivity (Scheme I & II). Furthermore we demonstrate an isomerisation of the precursor under UV irradiation obtaining all the enone Z,E isomers of the cascade precursor scaffold. We were able to obtain either a single Michael addition or a cyclisation, via transannular Diels Alder or Michael Michael cascade reaction depending on the configuration of the enones. These cascades undergo cyclisation in moderate to high enantioselectivity (Scheme II).